Konsep Komunikasi Lingkungan (Environmental Communication, Ecological Communication) - Nurul Mursida Siregar; Mhd. Latip Kahpi (PT. AHLAL PUBLISHER NUSANTARA, 2025)
Increasingly complex environmental crises require approaches that are not merely technical but also communicative, social, and cultural. This article aims to analyze the concepts of environmental communication and ecological communication and their relevance to sustainable development in the Indonesian context. This study employs a qualitative descriptive method through a literature review of academic books, scholarly journals, reports from national and international institutions, and environmental policy documents. The findings indicate that environmental communication plays a crucial role in raising public awareness, shaping attitudes, and encouraging community participation in environmental preservation. Meanwhile, ecological communication, as conceptualized by Niklas Luhmann, offers a critical perspective on how environmental issues are socially constructed and negotiated within communication systems involving political, economic, and cultural interests. In Indonesia, effective environmental communication practices are reflected in public campaigns, civil society advocacy, environmental journalism, and religion-based environmental movements. This article argues that the integration of environmental and ecological communication is a strategic instrument in supporting sustainable development and strengthening social and religious responsibility toward environmental sustainability. Keywords: Environmental Communication, Ecological Communication, Development Communication. Abstrak Krisis lingkungan yang semakin kompleks menuntut pendekatan yang tidak hanya bersifat teknis, tetapi juga komunikatif, sosial, dan kultural. Artikel ini bertujuan untuk menganalisis konsep komunikasi lingkungan dan komunikasi ekologi serta relevansinya dalam konteks pembangunan berkelanjutan di Indonesia. Penelitian ini menggunakan pendekatan kualitatif-deskriptif melalui studi literatur terhadap buku akademik, jurnal ilmiah, laporan lembaga nasional dan internasional, serta dokumen kebijakan terkait isu lingkungan. Hasil kajian menunjukkan bahwa komunikasi lingkungan berperan penting dalam meningkatkan kesadaran publik, membentuk sikap, dan mendorong partisipasi masyarakat dalam pelestarian lingkungan hidup. Sementara itu, komunikasi ekologi, sebagaimana dikembangkan oleh Niklas Luhmann, memberikan pemahaman kritis mengenai bagaimana isu-isu lingkungan dikonstruksi dan dinegosiasikan dalam sistem komunikasi sosial yang melibatkan kepentingan politik, ekonomi, dan budaya. Dalam konteks Indonesia, praktik komunikasi lingkungan yang efektif terlihat melalui kampanye publik, advokasi masyarakat sipil, jurnalisme lingkungan, serta gerakan dakwah berbasis nilai-nilai keagamaan. Artikel ini menegaskan bahwa integrasi komunikasi lingkungan dan komunikasi ekologi merupakan instrumen strategis dalam mendukung pembangunan berkelanjutan sekaligus memperkuat tanggung jawab sosial dan religius manusia terhadap kelestarian lingkungan. Kata kunci: Komunikasi Lingkungan, Komunikasi Ekologi, Komunikasi Pembangunan.